Structural brain abnormalities in schizophrenia in adverse environments: examining the effect of poverty and violence in six Latin American cities. (February 2021) - Crossley, Nicolas A.; Zugman, Andre; Reyes-Madrigal, Francisco; Czepielewski, Leticia S.; Castro, Mariana N.; Diaz-Zuluaga, Ana M.; Pineda-Zapata, Julian A.; Reckziegel, Ramiro; Gadelha, Ary; Jackowski, Andrea; Noto, Cristiano; Alliende, Luz M.; et al.
Summary: Background: Social and environmental factors such as poverty or violence modulate the risk and course of schizophrenia. However, how they affect the brain in patients with psychosis remains unclear. Aims: We studied how environmental factors are related to brain structure in patients with schizophrenia and controls in Latin America, where these factors are large and unequally distributed. Method: This is a multicentre study of magnetic resonance imaging in patients with schizophrenia and controls from six Latin American cities. Total and voxel-level grey matter volumes, and their relationship with neighbourhood characteristics such as average income and homicide rates, were analysed with a general linear model. Results: A total of 334 patients with schizophrenia and 262 controls were included. Income was differentially related to total grey matter volume in both groups ( P = 0.006). Controls showed a positive correlation between total grey matter volume and income ( R = 0.14, P = 0.02). Surprisingly, this relationship was not present in patients with schizophrenia ( R = −0.076, P = 0.17). Voxel-level analysis confirmed that this interaction was widespread across the cortex. After adjusting for global brain changes, income was positively related to prefrontal cortex volumes only in controls. Conversely, the hippocampus in patients with schizophrenia, but not in controls, was relatively larger in affluent environments. There was no significant correlation between environmental violence and brain structure. Conclusions: Our results highlight the interplay between environment, particularly poverty, and individual characteristics in psychosis. This is particularly important for harsh environments such as low- and middle-income countries, where potentially less brain vulnerability (less grey matter loss) is sufficient to become unwell in adverse (poor) environments.